KONVERGENSI MEDIA RADIO DALAM DUNIA DIGITAL: MENJAGA EKSISTENSI RADIO CB FM NEWS DENGAN APLIKASI SIARAN DIGITAL - Muhammad Rokib; Testa Pradia Nirwana; Febri Palupi Muslikhah (Fakultas Ilmu Dakwah dan Komunikasi, 2025)
This study aims to develop the CB FM News application as a solution to increase listener interest in the CB FM Rembang Radio Station, particularly among the community of Rembang Regency. Using a level 3 Research and Development (R&D) method, the development process includes planning, design, implementation, and system testing supported by appropriate hardware, software, and an engaging interface design to encourage the use of digital radio broadcasting. The research subjects consist of residents of Pasarean Village selected through simple random sampling. The findings show that the CB FM News application was successfully developed and tested without system bugs or errors, and it effectively integrates various media convergence features such as radio streaming, video streaming, news access, notifications, and user interaction. This innovation not only expands public access to information but also supports the digital transformation of CB FM Rembang Radio Station to remain relevant amid declining interest in conventional radio. Overall, the development of the CB FM News application provides an important contribution to sustaining the existence of local radio through the use of digital technology and the enhancement of user experience in accessing broadcast content.